2018
DOI: 10.3389/fimmu.2018.02604
|View full text |Cite
|
Sign up to set email alerts
|

Importance of EMT Factor ZEB1 in cDC1 “MutuDC Line” Mediated Induction of Th1 Immune Response

Abstract: The role of Epithelial to Mesenchymal Transition (EMT) factor Zeb1 is well defined in metastasis and cancer progression but it's importance in dendritic cells (DCs) is unexplored until now. For the first time we report here that Zeb1 controls immunogenic responses of CD8α+ conventional Type-I (cDC1) DCs. We found that ZEB1 expression increases significantly after TLR9 stimulation and its depletion impairs activation, co-stimulation and secretion of important cytokines like IL-6, IL-10 and IL-12 in cDC1 MutuDC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 90 publications
1
31
0
Order By: Relevance
“…To determine the role of NCoR1 in DCs, we have developed a stable NCoR1 knockdown (KD) and matched empty vector-transduced control cells using lentiviral short hairpin RNA (shRNA) approach in a CD8α + cDC1 DC line that mimics remarkably the ex vivo isolated cDC1 DCs (Fuertes Marraco et al., 2012, Smita et al., 2018). We found that NCoR1 transcript levels were significantly reduced (≥85%) in NCoR1 shRNA-transduced DCs (Figures 1A and S1A).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the role of NCoR1 in DCs, we have developed a stable NCoR1 knockdown (KD) and matched empty vector-transduced control cells using lentiviral short hairpin RNA (shRNA) approach in a CD8α + cDC1 DC line that mimics remarkably the ex vivo isolated cDC1 DCs (Fuertes Marraco et al., 2012, Smita et al., 2018). We found that NCoR1 transcript levels were significantly reduced (≥85%) in NCoR1 shRNA-transduced DCs (Figures 1A and S1A).…”
Section: Resultsmentioning
confidence: 99%
“…They can have both inductive and repressive features at the same time, depending on whether they induce an epithelial or mesenchymal phenotype [ 116 ]. As they are responsible for the maintenance of the epithelial or mesenchymal phenotype, respectively, they are also expressed to a varying degree, depending on the cell type, in normal tissues [ 117 , 118 ].…”
Section: Emtmentioning
confidence: 99%
“…Recently, one study examined the role of ZEB1 in the murine tumorderived DC cell line (MutuDC) [19] previously reported to resemble splenic cDC1s [20]. This study found that knocking down Zeb1 in MutuDCs led to their impaired activation upon stimulation with the toll-like receptor 9 (TLR9) agonist CpG, and CpG-activation of Zeb1-deficient MutuDCs skewed T cell differentiation towards a Th2 rather than a Th1 response; relative to controls, this was evidenced by a slight increase in GATA3 + interleukin (IL)-13 + Th2 cells and reduced T-bet + IFN-g + Th1 cells following DC:T cell coculture [19] (Figure 3). Transient Zeb1-deletion in mouse Flt3Lderived CD11c + CD24 + bone marrow-derived dendritic cells (BMDCs) also resulted in impaired cytokine secretion upon stimulation with CpG compared with WT controls [19].…”
Section: Zeb1 In Dendritic Cellsmentioning
confidence: 99%
“…This study found that knocking down Zeb1 in MutuDCs led to their impaired activation upon stimulation with the toll-like receptor 9 (TLR9) agonist CpG, and CpG-activation of Zeb1-deficient MutuDCs skewed T cell differentiation towards a Th2 rather than a Th1 response; relative to controls, this was evidenced by a slight increase in GATA3 + interleukin (IL)-13 + Th2 cells and reduced T-bet + IFN-g + Th1 cells following DC:T cell coculture [19] (Figure 3). Transient Zeb1-deletion in mouse Flt3Lderived CD11c + CD24 + bone marrow-derived dendritic cells (BMDCs) also resulted in impaired cytokine secretion upon stimulation with CpG compared with WT controls [19]. Although these results suggest that ZEB1 may play a role in modulating DC activation and the subsequent induction of T cell responses, in this study the effect of deleting Zeb1 on the development of cDC1s was not addressed and remains to be determined.…”
Section: Zeb1 In Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation